Evaluation of Macrophyte Community Dynamics (2015–2020) in Southern Lake Garda (Italy) from Sentinel-2 Data - Nicola Ghirardi; Mariano Bresciani; Gary Free; Monica Pinardi; Rossano Bolpagni; Claudia Giardino (Applied Sciences, 2022)
Macrophytes are of fundamental importance to the functioning of lake ecosystems. They provide structure, habitat, and a food source and are a required component in monitoring programs of lake ecological quality. The key aim of this study is to document the variation in spatial extent and density of macrophytes seasonally between 2015 and 2020 of the Sirmione Peninsula (Lake Garda, Italy), using Sentinel-2 imagery. In addition to this, our results were compared to previous data from imaging spectrometry; individual parameters affecting macrophyte communities were tested, and the possible effect of the COVID-19 lockdown on macrophyte colonization was evaluated. Satellite images allowed the mapping of the spatiotemporal dynamics of submerged rooted macrophytes in order to support monitoring of the shallow water ecosystem under study. Substantial changes were found in both spatial extent and density over the period from 2015 to 2020, particularly in 2019 when there was almost a complete absence of dense macrophytes. Variables found to influence the amount of macrophytes included transparency, chlorophyll–a, water level, winter wave height, and grazing by herbivores. A separate analysis focusing on areas associated with boat transit found a recovery in macrophyte coverage during the period of COVID-19 lockdown. The outcome of the study highlights a decline in the density of the macrophytes and a shift towards deeper areas compared to the situation in 1997. The area examined is part of an internationally important site containing the highest abundance and diversity of overwintering water birds in Italy. Exploiting satellite data at high frequency provided an insight to understand the dynamic changes and interactions with herbivorous birds, environmental factors, and anthropogenic pressures, revealing a delicately balanced and threatened ecosystem.